2017
DOI: 10.1007/s10875-017-0403-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 22q11.2 Deletion Syndrome via Newborn Screening for Severe Combined Immunodeficiency

Abstract: Our findings support rapidly screening infants with a positive NBS for SCID, but without SCID, for 22q11.2DS even when typically associated features such as CHD are absent, particularly when B cells and NK cells are normal. Moreover, direct NBS for 22q11.2DS using multiplex qPCR would be equally, if not more, beneficial, as early identification of 22q11.2DS will obviate a protracted diagnostic odyssey while providing an opportunity for timely assessment and interventions as needed, even in the absence of T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 31 publications
1
28
0
3
Order By: Relevance
“…These infants will require a matched sibling T cell transfer or a thymus transplant . The use of newborn screening for severe combined immunodeficiency has led to improved recognition of these infants and we demonstrated that unbiased testing led to early identification of infants who would not otherwise have been identified …”
Section: Managementmentioning
confidence: 79%
See 3 more Smart Citations
“…These infants will require a matched sibling T cell transfer or a thymus transplant . The use of newborn screening for severe combined immunodeficiency has led to improved recognition of these infants and we demonstrated that unbiased testing led to early identification of infants who would not otherwise have been identified …”
Section: Managementmentioning
confidence: 79%
“…Overall, syndromes as a general category are the most frequent final diagnosis to explain low T cell counts . We examined whether infants with 22q11.2del could be reliably identified through newborn screening for severe combined immunodeficiency . Although the sensitivity of the current newborn screening for severe combined immunodeficiency for 22q11.2del is low, approximately half of the patients identified in this way would not likely have been picked up in the newborn period otherwise.…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 47 cases of DiGeorge Syndrome, 9% received a thymus transplant while the other 90% had partial DiGeorge syndrome with improving T cell function over time [21]. In a separate study of patients diagnosed with 22q11.2 Deletion Syndrome, the most common cause of DiGeorge, 45% of patients were diagnosed prior to the screening result [53]. These results show that there may be some benefit to patients who would not have been diagnosed either symptomatically or through a family history prior to the TREC screening result.…”
Section: Discussionmentioning
confidence: 99%